Studi Kupu-kupu (Lepidoptera : Rhopalocera) di Daerah Papua Barat - Adinda Carissa; Nadia Azzahra; Sekar Ayu Pamela; Ade Suryanda (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2024)
Research on butterflies (Lepidoptera: Rhopalocera) in the West Papua area was carried out to determine the species of butterflies in the area. This observation uses the literature study method, namely several steps carried out regarding the collection of library data from several trusted journals, where the observations rely on various literature to obtain research data and extract core information in the form of descriptions. The total number of Rhopalocera species in the Papilionoidea Superfamily is 391 with species from the Nymphalidae Family dominating the West Papua area. Cyrestis acilia is the most commonly found species with 66 species. The Nymphalidae family is most commonly found because it is polyphagous, so it has quite high adaptability compared to other families.